2022
DOI: 10.1038/s41421-022-00400-7
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA regulates chromosome clustering during mitosis

Abstract: Noncoding RNAs are known to associate with mitotic chromosomes, but the identities and functions of chromosome-associated RNAs in mitosis remain elusive. Here, we show that rRNA species associate with condensed chromosomes during mitosis. In particular, pre-rRNAs such as 45S, 32S, and 30S are highly enriched on mitotic chromosomes. Immediately following nucleolus disassembly in mitotic prophase, rRNAs are released and associate with and coat each condensed chromosome at prometaphase. Using unbiased mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, our findings support the notion that Ki-67’s interaction with RNA is key to phase separation and chromosome clustering. Several studies suggested that Ki-67 interacts either directly or indirectly with RNA: Recent reports showed that Ki-67 depletion caused loss of newly synthesized RNAs from chromosomes in early mitosis 7 , that recombinantly expressed fragments of Ki-67 such as the fork-head associated (FHA) domain or three tandem repeats pulled down pre-rRNAs from total RNA 26 , and that the FHA domain interacted with the putative RNA-binding protein NIFK 27 . Since the latter interaction was dependent on mitotic phosphorylation, it is, however, unlikely that NIFK binding contributes to RNA recruitment during mitotic exit.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our findings support the notion that Ki-67’s interaction with RNA is key to phase separation and chromosome clustering. Several studies suggested that Ki-67 interacts either directly or indirectly with RNA: Recent reports showed that Ki-67 depletion caused loss of newly synthesized RNAs from chromosomes in early mitosis 7 , that recombinantly expressed fragments of Ki-67 such as the fork-head associated (FHA) domain or three tandem repeats pulled down pre-rRNAs from total RNA 26 , and that the FHA domain interacted with the putative RNA-binding protein NIFK 27 . Since the latter interaction was dependent on mitotic phosphorylation, it is, however, unlikely that NIFK binding contributes to RNA recruitment during mitotic exit.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR products were visualized by agarose (2%) gel electrophoresis. Subcellular fractions were confirmed by respective fraction markers: Gapdh and RNA18S (cytoplasmic markers), Malat1 (nuclear markers), and RNA45S (chromatin markers), since 45S rRNA is chromosome-associated [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed using NETN100 buffer (25 mM Tris-HCl pH 7.5, 100 mM NaCl, 0.5% Nonidet P-40, 1 U/μl RNase inhibitor, 100 mM PMSF) ( 26 , 27 ). The lysate was centrifuged at 2000 g at 4°C for 20 min to separate the NETN100 soluble and pellet fractions.…”
Section: Methodsmentioning
confidence: 99%